A Comparative Study of Selected Assamese and English Medium Pre-Schools in Guwahati - Saha, Kaberi; Changkakati, Ananya (JOURNAL OF INDIAN EDUCATION, 2010)
Assam has made considerable progress in pre school education during the last five years. In the recent years, a number of franchised English Medium School and also a number of Assamese medium pre schools like have also grown up. The investigator found it necessary to make a comparative study on these two types of (medium) pre schools, as pre-school is the base for the all round development of the children. The present study has been conducted in Guwahati City of Assam and the data has been collected from 18 head masters/mistresses through interview and 36 school teachers through questionnaire from the selected 18 sample schools. The main aim was to make a comparative study about the status of those selected two types (medium) of schools (Eng. =9, As.=9). The other objective was to make a comparative study in respect of school activities, teaching equipments, evaluation, teacher’s training etc. The results indicate that, in both types of schools there are lack of facilities, trained teachers, infrastructure etc. However, it is revealed that, English medium schools provides better activities for developing motor, gross motor, social and emotional development, language, alphabet, numbers as well as the sense training than that of the Assamese medium schools. English medium schools have better equipment, infrastructure, trained teacher, evaluating procedure than that of the Assamese medium schools. Both types of school are however lagging behind in fulfilling the overall objective of pre primary education.